Model of Civic Education as Moral Education - Ryan Prayogi; Sapriya Sapriya; M. Januar Ibnu Adam; T Heru Nurgiansah (ASANKA : Journal of Social Science and Education, 2024)
This research examines the importance for civic education teachers in carrying out the learning process in class not only achieving cognitive aspects but every teacher must also prioritise affective aspects in the learning process, so that using the Moral Education model in Civic Education can be a reference for teachers in carrying out Civic Education learning by using the Moral Education model as an effort to foster Moral feeling, Moral Behaviour and Moral action. The purpose of this research is how Citizenship Education as Moral Education and the Development of Moral Education models in Citizenship Education. While this research method uses a literature study research approach with steps to select themes, search for references, collect data sources, and analyse data and draw conclusions. The results showed that education as moral education has existed since civic education entered Indonesia, and that the development of moral education models in civic education, one of which uses the Human Modelling model and Value Clarification Technique, provides a practical solution for civic education as moral education that refers to the 21st century learning model.